OBSTACLE TO FAMILY HARMONY: PSYCHOLOGICAL CONSEQUENCES OF CONFLICTS AND WAYS OF ELIMINATION - Kholmirzayeva Munisa Saidjonovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In this work, ways to maintain family harmony and resolve conflicts are analyzed. The work focuses on the psychological and social causes of family conflicts and their consequences. Among them, the role of communication culture, psychological methods of listening, family therapy, and counseling services is highlighted. Stress management techniques and practical recommendations for ensuring emotional stability are presented. Strategies for conflict resolution and the development of preventive measures were also considered. The work emphasizes the importance of family harmony for the stability of society.